The Red River Resistance of 1869--1870: The Machiavellian moment of the Metis of Manitoba - O'Toole, Darren (University of Ottawa (Canada), 2010)
In October 1869, the fledgling Canadian federation was preparing for the transfer of Rupert's Land and the Northwestern Territory when the Metis set up a Provisional Government in order to resist what they saw as a unilateral annexation of their homeland. Although there were multiple references made to 'republicanism' during the Resistance, no scholar has ever explored whether republican conventions were actually present in political discourse in the District of Assiniboia prior to the Resistance and whether they were effectively activated during the Resistance. Working from the Cambridge School approach of discourse analysis, it first identifies the conventions of democratic rhetorical republicanism, which includes positive and negative liberty, the rule of law, the mixed and balanced constitution and citizenship, which in turn involves virtue, the militia and real property. It then looks at the gradual introduction in Assiniboia of republican discourse from multiple sources, including the United States, Lower Canada, Upper Canada, Ireland, France and Great Britain and its circulation throughout several practical political struggles during the period from 1835 to 1869. In doing so, it shows that certain 'organic intellectuals' acted as 'transmission belts' of republican conventions and that institutional structures were a factor that rendered the activation of such conventions almost inevitable. By the time the Resistance took place in 1869, a more or less fully developed republican paradigm formed part of the linguistic matrix and was available to political actors in Assiniboia. Finally, the thesis shows that republican discourse was effectively mobilised by identifying fragments of republican conventions that were harnessed in various speech-acts during the Resistance. It is argued that republican language was fundamental to the success of the ideological and political manoeuvres of the leaders of the Resistance as it was particularly effective both as an instrument of anti-colonialism and as a pragmatic ideal of self-government that sought to correct the iniquities of colonial government.
Keywords: History, Canadian.; Political Science, General.; Native American Studies.